The Empowerment of Small Enterprises in Construction Sector for Government Procurement of Goods and Services: Mandatory Study of Role and Risk - Kamal, Mustofa; Elim, john (KINERJA, 2020)
This study aims to investigate the empowerment of small enterprises in construction sector and the risks since the issuance of Perpres No.16 Year 2018 and PermenPUPR No 7 Year 2019. The accuracy of the procurement and the development of small-medium enterprise role have been parts of the objectives of government procurement. Then, the policy states that government should give opportunities to small enterprises. Qualitative study was conducted using the approach of applied law research. Literature study and observation on the stake holders were done. The results showed that small enterprises in construction sector played more roles with the procurement package up to Rp 10,000,000,000.00 (ten billion rupiah). However, the implementation in 2018 showed that the role of small enterprises declined compared to the previous year, the participation of small enterprises in construction sector was still low compared to non-small enterprises. Besides that, the small enterprises that received the procurement package were prone to criteria violation of small enterprises as in UU No. 20 Year 2008 about micro, small and medium enterprises (MSME). The identified risk was that the small enterprises received the package for small enterprises in construction sector. This risk should be maintained and handled by procurement agents through effective qualification verification, by government instances that issue the construction permit by developing the potency of the small enterprises to level up, and government instances through association of construction enterprises by cooperating in building good governance in the management of construction procurement.Keywords: small enterprises, empowerment, risks, good governance